Employee Relations dan Corporate Reputation Belajar dari Google - Isabella Astrid Siahaya (Jurnal InterAct, 2013)
Nowadays companies highly acknowledge the significant role of employee to improve company’s performance. As important as it is, in Indonesia, companies are publicize actively their relationship with their employees. An Indonesia’s leading newspaper ran an article covering companies that provide attractive facilities that employees can use  in their  office. Also described  is how  every company tries to make their employees feel comfortable at work, treat them well and make them happy which at the end contribute to increase productivity. This article, particularly, discusses about how employee relation is used to build and improve company’s reputation.